Adverse Drug Reactions of Lithium Monotherapy in Bipolar Affective Disorder: An Observational Study in Eastern Nepal: Adverse Drug Reactions of Lithium Monotherapy in Bipolar Affective Disorder: An Observational Study in Eastern Nepal - Sarraf, Dr. Deependra Prasad (International Journal of Pharmaceutical & Biological Archive, 2021)
Introduction: Lithium is the most effective long-term therapy for bipolar affective disorder (BPAD). Its therapeutic benefits may be restricted by frequent adverse drug reactions (ADRs) and low therapeutic index. We evaluated the pattern of ADR of lithium monotherapy in patients with BPAD. Materials and Methods: An observational study was conducted in 213 patients presenting to psychiatric outpatient department and diagnosed with BPAD and taking lithium monotherapy at least for 3 months. Data collection was done from December 15, 2018, to December 14, 2019. Sociodemographic profile, relevant laboratory investigations, and ADRs were recorded on a self-designed proforma. Descriptive statistics were used to analyze the data. Chi-square test was used to correlate the association between ADR and baseline variables using Statistical Package for the Social Sciences (Version 22.0). P < 0.05 was considered statistically significant. Results: Out of 213 patients, 110 (51.6%) were male. Mean age was 32.06 Â± 1.80 years. Sixty-nine (32.4%) patients were substance user. The prescribed dose of lithium ranged from 300 to1200 mg/day. At least one ADR was observed in 139 (65.3%) patients. Tremor (45%) was the most common ADR followed by nausea (9.5%) and sedation (7.8%). Discussion: Daily administration of lithium 1000 mg or more was found to be a significant risk factor for occurrence of the ADRs. Weight gain might result in lithium non-compliance and hence the patients must be counseled regarding this to improve medication adherence. Conclusion: The prevalence of ADR was high in the patients taking maintenance dose of lithium. The patients need regular follow-up to detect and manage ADR which help to increase the medication adherence. There is an urgent need of active pharmacovigilance to detect the ADR in the patients with BPAD.